SOCIAL AND EMOTIONAL COMPETENCIES OF FUTURE PUPILS OF THE 1ST YEAR OF PRIMARY SCHOOL - Kruszewska, Aleksandra (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
Despite many works concerning school maturity in Poland, there are only few that focus only on emotional aspects of social behaviours of children who are to start school education. Interest in this issue started increasing when educational authorities announced lowering the age of compulsory education. Majority of available studies concerns evaluation and abilities of children referring to their cognitive possibilities. Although they are very important for the children’s further development, the reasons for success are rather related to emotional and social intelligence. This article presents the research results concerning socio‑emotional competenciesof future pupils of the first year of primary school. Pedagogical observation comprises children from two years remaining at preschool before starting school education. The goal of the study was to present social and emotional state of the 6- and 7-year-old children after cancellation of, so called, “six-year-olds law”.